Two New Types of Fixed Point Theorems in Complete Metric Spaces - Farshid Khojasteh; Mujahid Abbas; Simona Costache (Abstract and Applied Analysis)
We introduce two new types of fixed point theorems in the collection of multivalued and single-valued mappings in complete metric spaces.